Kajian Al-Maidah Ayat 64-71 Tentang Pendidikan: Metode Kisah Dan Gaya Komunikasi Dalam Pendidikan Islam - Wahyudin Noor Noor (Tarbawy : Jurnal Pendidikan Islam, 2017)
Surat al-Maidah: 64-71 tells two important things: first, the story of the Jews who were cursed by Allah because of bad speech born from envy and hatred against Prophet Muhammad SAW. Second, the obligation of Prophet Muhammad SAW in conveying Islam. These two things, if attributed to the context of Islamic education, will imply the existence of messages of Islamic education; the message of an educational method that is the method of story in one side, and on the other side describes the instructions of communication.